Pengembangan Buku Panduan Program Merancang Website Berbasis CMS Wordpress Bagi Guru - Mutoharoh, Mutoharoh; Muliyati, Dewi; Amada, Early (MJI Publisher by PT Mitra Jurnal Indonesia, 2022)
Abstract CMS is an application that manages, edits, and publishes web content. The CMS interface is more visually enabling without coding, thus enabling teachers to develop websites. Teachers can build websites personally and be used to support careers. These online pages can be used to make portfolios, take online classes, and publish papers. This research aims to develop a guidebook that teachers can use in designing WordPress CMS-based websites. This time, the research and development method or Research and Development (RnD). The research model used is 4D Thiagarajan, it's just that the stage is used until developed. The results of this research are in the form of a book,